The extent to which employers are implementing the Code of Good Practice on HIV/AIDS, as it relates to the Employment Equity and Labour Relations Acts - Van Heerden, Magda (University of Pretoria, 2013)
Dissertation (MSD (Social Work Management))--University of Pretoria, 2006.